The Role of Ultrasound Across the Inflammatory Arthritis Continuum: Focus on “At-Risk” Individuals - Duquenne, Laurence; Chowdhury, Rahaymin; Mankia, Kulveer; Emery, Paul (Frontiers in Medicine, 2020)
In individuals at-risk of developing inflammatory arthritis, the value of an ultrasound (US) scan assessment to predict progression has been demonstrated repeatedly. However, depending on recruitment criteria, these individuals may be at different stages in the arthritis development continuum, therefore representing a heterogeneous population. As a consequence, the predictive value of ultrasound results may differ between cohorts. As other reviews have focused on the challenges in population recruitment or have combined biomarkers predicting value according to one recruitment pathway, we wanted to focus on the sole use of ultrasound assessment and its variation according to population recruitment criteria. In this review, we discuss the use of ultrasound in the different at-risk populations across the inflammatory arthritis disease continuum. This review demonstrates that although some sub-population data is scarce, ultrasound is best predictive in three at-risk populations: those with a positive ACPA test in the context of non-specific MSK symptoms, those with clinically suspect arthralgia and those with palindromic rheumatism. We consider that ultrasound assessment will be a cornerstone in prediction risk modeling and prevention studies of the preclinical phases of IA in the future.